Model Hidrologi Untuk Analisis Ketersediaan Air Di Daerah Aliran Sungai (DAS) Tapung Kiri Menggunakan Data Satelit - Fian Syauqi; Sigit Sutikno; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The land use changes at Tapung Kiri watershed can affected the groundwater availability and affecting the fluctuations of rivers flow. Therefore, to develop strategies for a comprehensive watershed management, it is required a hydrological model that can represent the hydrological cycle of watershed. Hydrological model was performed by using SWAT tool. The SWAT simulations was performed in various scenarios for land use changes in the period of 2002, 2007 and 2012. Land use map that used as an input to SWAT were Landsat images that processed by the Supervised Classification method. Based on the results of this study, the most optimal value of coefficient of determination (R2) is 0,62 and the value of Nash Sutcliffe Efficiency (NSE) is 0,62. Process of validation obtained coefficient R2 = 0,51 and NSE = 0,40. These results have satisfied the research objectives as the findings coefficient were > R2 min 0,4, and >NSE 0,35. Analysis of groundwater availability was conducted by comparing the ratio of Qmaximum and Qminimum during 2002 to 2012. Comparison of obtained ratio value were 5,53 (2002), 11,22 (2007), and 8,68 (2012). If the value ratio Qmaximum / Qminimum was bigger, then groundwater availability increasingly critical. Therefore, changes of land use at Tapung Kiri watershed can cause groundwater reserves increasingly critical.Keywords: Land use change, SWAT model, groundwater availability.